Prophetic religions and politics Religion and the political order, vol. 1 - Hadden, Jeffrey K.; Shupe, Anson D. (New York Paragon House, 1986)
Papers presented at an international conference, held in Nov. 1984, in Martinique. "A New ERA book." Includes bibliographies and index.
Keywords: Religion and politics -- Congresses. Religion and politics